Avaliação da atividade antiviral do BromAc® para o tratamento da COVID-19 - Linziane Lopes Ferreira (2023)
COVID-19 is one of the most significant challenges facing modern civilization and has not yet been eradicated. SARS-CoV-2 is a virus that can mutate and evade the antibodies generated by viral exposure or vaccination and, as a result, SARS-CoV-2 remains an imminent threat to public health. Currently, there is no 100% effective antiviral treatment for the severe form of COVID-19. Although treatment with dexamethasone and mechanical ventilation is the standard procedure for treating the disease, some patients still succumb to the infection. In this regard, BromAc® is a combination of bromelain and N-acetylcysteine, which has shown mucolytic effect and robust anti-inflammatory properties. Therefore, in the present study, we performed in vitro and ex vivo analyses to evaluate the effect of bromelain in combination with N-acetylcysteine on virus containment at different levels. The results indicated virucidal and dose-dependent activity of the combined compounds in vitro on the Vero-ACE2/TMPRSS2 cell line infected with the ômicron variant. In addition, the combined compounds reduced the number of genomic copies of SARS-CoV-2 RNA in tracheal aspirate samples from severely ill COVID-19 patients. BromAc® also promoted the cleavage of the S1 subunit of the Spike protein in tracheal aspirate samples, which brings new evidence of antiviral activity in samples from COVID-19 patients. In summary, these results bring to light evidence of ex vivo antiviral activity of the combination of bromelain and N-acetylcysteine that suggests its potential as a nebulization approach for treating COVID-19.